Induced pluripotent stem cell modeling of Gaucher's disease: what have we learned? - Santos Matias, Dino (2018)
Gaucher's disease (GD) is the most frequently inherited lysosomal storage disease, presenting both visceral and neurologic symptoms. Mutations in acid beta-glucocerebrosidase disrupt the sphingolipid catabolic pathway promoting glucosylceramide (GlcCer) accumulation in lysosomes. Current treatment options are enzyme replacement therapy (ERT) and substrate reduction therapy (SRT). However, neither of these approaches is effective in treating the neurological aspect of the disease. The use of small pharmacological compounds that act as molecular chaperones is a promising approach that is still experimental. In recent years, an association between GD and Parkinson like synucleinopathies has been discovered. Since 1992, a number of mouse models of GD have been the developed and partially reproduce phenotype of the disease. More recently, the discovery of direct reprograming has allowed the derivation of induced pluripotent stem cells (iPSc) from fibroblasts obtained from GD patients. iPSc can be expanded indefinitely in vitro and differentiated to macrophages and neurons, the main relevant cell types involved in GD. In this work, we review iPSc models of GD and summarize what we have learned from this system.